(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Community-Based Ecotourism (CBET) has emerged as a key strategy for integrating environmental sustainability, community empowerment, and local economic development, particularly in ecologically sensitive regions like the Eastern Himalayas. This study evaluates the sustainability performance of three CBET sites in Sikkim—Darap, Pastanga, and Kitam—using the Triple Bottom Line (TBL) framework. Through a comparative case analysis supported by document-based qualitative methods, field reports, and policy review, the research highlights how governance structures, institutional durability, and spatial positioning shape CBET outcomes. The findings reveal that Darap’s participatory, community-led model fosters balanced sustainability; Pastanga, once externally supported, suffers from institutional withdrawal and systemic decline; and Kitam, governed under state conservation, achieves ecological goals but limits social and economic inclusion. The study argues that sustainability in CBET is not an inherent feature of ecotourism but a negotiated process contingent upon adaptive governance, reinvestment mechanisms, and local agency. Policy recommendations emphasize hybrid models that decentralize decision-making while ensuring regulatory and infrastructural support. This research contributes to both ecotourism theory and practice by advancing a nuanced understanding of how CBET functions within complex socio-institutional ecologies in mountain regions.